Disruptive Behaviors and Social Networks (Docentes 2.0 Journal, 2026)
The development of information and communication technologies transformed young people’s forms of social interaction, particularly in university contexts, where social media became spaces for socialization, academic exchange, and identity construction. However, its intensive use also generated risks associated with digital dependency, constant exposure, and the emergence of disruptive behaviors. The objective of the research was to understand the influence of social media as a triggering factor for disruptive behaviors among university students. The study was framed within the humanistic paradigm, under the hermeneutic method, with a qualitative approach, a topical narrative design, an informative documentary scope, and a cross-sectional timeframe. The population consisted of scientific documents related to social media and disruptive behaviors among young university students; through selective sampling, 34 documents were retrieved from Google Scholar, SciELO, Web of Science, and ScienceDirect. Source and category triangulation was used as the technique, a documentary analysis matrix was applied as the tool, and a dialectical-hermeneutic analysis was conducted to interpret the findings. The results showed that intensive social media use was associated with digital dependency, the search for external validation, loss of self-control, anxiety, and irritability. Likewise, digital anonymity favored manifestations such as cyberbullying, offensive comments, and the activity of “haters.” It was concluded that social media constituted relevant spaces for academic and social interaction; nevertheless, its unregulated use increased vulnerability to harassment dynamics. Therefore, strengthening cybersecurity, digital self-regulation, and socio-emotional skills in university education was required.
Keywords: Social Media; internet; disruptive behaviors; bullying; college students